Effects of red light on sleep and mood in healthy subjects and individuals with insomnia disorder - Pan, Rong; Zhang, Guimei; Deng, Fangyi; Lin, Weifeng; Pan, Jiyang (Frontiers in Psychiatry, 2023)
Introduction This study aimed to determine the influence of red light on objective sleep and the relationship between mood and sleep among individuals with insomnia disorder (ID). Method 57 individuals with insomnia symptoms and 57 healthy participants were randomly divided into three groups (red- and white-light groups, and the black control group), which received different light treatments for 1 h before bedtime. The emotions and subjective alertness of participants were evaluated using Positive and Negative Affect Schedule scales (PANAS) and Karolinska Sleepiness Scale (KSS), their sleeping data were recorded using polysomnography (PSG). Result The negative emotion scores were higher in the healthy subject-red light (HS-RL) group than in the HS-white light (WL) and HS-black control (BC) groups (p < 0.001). The anxiety and negative emotion scores were higher in the ID-RL group than in the ID-WL and ID-BC groups (p = 0.007 and p < 0.001, respectively). The KSS scores were lower in the RL group than in the WL and BC groups for both HS and ID group (both p < 0.001). The SOL was shorter in the HS-RL group than in HS-WL group (p = 0.019). Compared with the HS-BC group, the HS-RL group had an increase in microarousal index (MAI) and N1% (p = 0.034 and p = 0.021, respectively), while the total sleep time (TST) and sleep efficiency (SE) decreased (p = 0.001 and p < 0.001, respectively). Compared with the ID-WL group, the SOL was shorter in the ID-RL group (p = 0.043), while TST, SE, number of microarousals (NMA), and numbers of cycles of REM period were increased (p = 0.016, p = 0.046, p = 0.001, and p = 0.041, respectively). Compared with the ID-BC group, the ID-RL group had increases in the SOL, WASO, and the numbers of cycles and NMA in REM period (p = 0.038, p = 0.005, p = 0.045, and p = 0.033, respectively), and a decrease in SE (p = 0.014). The effects of ID-WL (vs. ID-RL group) and ID-BC (vs. ID-RL group) on SOL were mediated by negative emotions (mediating effects were − 37.626 and − 33.768, respectively). Conclusion Red light can increase subjective alertness, anxiety, and negative emotions in both healthy subjects and people with ID, which can affect sleep directly or indirectly via the mediating effect of negative emotions.